2000
DOI: 10.1007/bf02859455
|View full text |Cite
|
Sign up to set email alerts
|

Hazard analysis and critical control points of weaning foods

Abstract: Hazards and critical control points were identified during the preparation, feeding and storage of weaning foods fed to the children (6-24 months) belonging to low income group (LIG) families using survey methods, spot and indepth observations and microbial analysis. High microbial counts were obtained for the weaning food samples procured from the families that were rated as poor for both personal hygiene and environmental sanitation. Food samples that were held at ambient temperature (25-35 degrees C) showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
5
14
1
Order By: Relevance
“…Sources of potential contamination identified for both Moni and Fish Soup were consistent with those found by similar studies conducted in developing countries (Bryan, 1992;Ehiri et al, 2001;Sheth et al, 2000). Most food preparation and handling operations were exposed at the same time to all of the potential hazards listed (Table 1), as is typical of low-income settings (Madhu, Sukhbir, Sunita, & Chhibber, 1996).…”
Section: Describing the Processes Of Food Preparation And Handlingsupporting
confidence: 77%
See 3 more Smart Citations
“…Sources of potential contamination identified for both Moni and Fish Soup were consistent with those found by similar studies conducted in developing countries (Bryan, 1992;Ehiri et al, 2001;Sheth et al, 2000). Most food preparation and handling operations were exposed at the same time to all of the potential hazards listed (Table 1), as is typical of low-income settings (Madhu, Sukhbir, Sunita, & Chhibber, 1996).…”
Section: Describing the Processes Of Food Preparation And Handlingsupporting
confidence: 77%
“…Bryan (1992) mentioned in his review 3 CCPs for canned milk: boiling water, milk-can opening and storage. Sheth et al (2000) found 2 CCPs for Chappati foods: roasting and holding at ambient temperature. Ehiri et al (2001) found 3 CCPs for Jollof rice, Moiemoi and Agidi, including cooking and reheating, and 2 CCPs for Ground crayfish including handling.…”
Section: Identification Of Ccpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Communities from other low-income countries also practiced similar food preparation processes with direct hand contact. 9,23,28 Unwashed hands, contaminated from contact with other foods (crosscontamination) during cooking or through fecal contact (e.g., defecation, handling cow dung, cleaning the household) that occurred during cooking, can be sources of enteric pathogens. On the basis of frequency of hand contact, crosscontamination opportunities, and level of moisture content, Food preparer went to toilet Food preparer was cutting vegetables for cooking.…”
Section: Discussionmentioning
confidence: 99%